An integrated hot stamping forming method for a super-large automobile double-door ring

By using an amorphous metaphosphate-borate composite ceramic lubricating protective layer during the hot stamping process of ultra-large automotive double door rings, the problems of surface oxidation and decarburization were solved, thereby improving the surface quality and performance of parts at high temperatures, reducing the coefficient of friction, and increasing production efficiency.

CN123039713APending Publication Date: 2026-11-06JINGJIANG XINCHENG VEHICLE PARTS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610889541.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing hot stamping technology suffers from surface oxidation and decarburization problems when producing ultra-large automotive double door rings. Existing solutions, such as Al-Si coating, are costly or have uneven coatings, and cannot effectively solve the high-temperature oxidation/decarburization problem, thus affecting production efficiency.

Method used

An amorphous metaphosphate-borate composite ceramic lubricating protective layer is formed by coating with an aqueous suspension precursor liquid. Through a cascade chemical reaction, a uniform and dense protective layer is generated in situ on the steel plate surface, which avoids oxide scale and decarburization, reduces the coefficient of friction, and improves surface hardness and bending fatigue life.

Benefits of technology

It effectively isolates oxygen and carbon atom diffusion at high temperatures, ensuring part surface quality, reducing the coefficient of friction, improving surface hardness and bending fatigue life, and increasing production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

This invention discloses an integrated hot stamping forming method for ultra-large automotive double door rings, comprising the following steps: S1, cleaning; S2, coating with a precursor; S3, drying; S4, in-situ reaction and austenitization; S5, hot stamping and quenching. This invention coats the surface of the welded plate with a precursor liquid, which can be in-situ transformed into a uniform, dense amorphous metaphosphate-borate composite ceramic lubricating protective layer. This avoids surface decarburization and oxide scale formation, significantly reduces the friction coefficient between the sheet and the die, and ensures that the double door ring parts have excellent surface hardness, bending fatigue life, and high-temperature self-lubricating properties after hot stamping.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of hot stamping technology, and in particular relates to an integrated hot stamping forming method and system for ultra-large automotive double door rings. Background Technology

[0002] With the automotive industry's ever-increasing demands for lightweighting and collision safety, hot stamping has become the mainstream process for producing ultra-high-strength body structural components. Based on this technology, integrated door ring technology, which combines multiple components such as the A-pillar, B-pillar, and door sill into a large double-ring structure, is gradually becoming a cutting-edge solution for high-end and new energy vehicles due to its ability to effectively reduce the number of parts and welding processes, achieve significant weight reduction, and improve overall structural rigidity.

[0003] However, existing hot stamping technology, especially for the production of integrated large door rings, still faces a series of technical bottlenecks that urgently need to be addressed. Firstly, surface oxidation and decarburization during the hot stamping process are core challenges in the industry. When steel sheets undergo austenitization at temperatures above 900°C in a furnace, the iron on their surface reacts violently with oxygen in the furnace atmosphere, generating a loose oxide scale. Simultaneously, carbon on the steel sheet surface is burned off due to diffusion, forming a decarburized layer. The presence of oxide scale not only deteriorates the surface quality of the workpiece, increasing the cost and time of subsequent shot peening or pickling processes, but may also lead to accelerated die wear. More seriously, the decarburized layer significantly reduces the surface hardness, fatigue limit, and wear resistance of the parts, directly posing a safety hazard for door rings, which are structural components of vehicle bodies.

[0004] To address the aforementioned issues, existing technologies primarily employ two approaches. One is to use aluminum-silicon coated steel sheets. This involves pre-plating an aluminum-silicon alloy onto the steel sheet surface, which reacts with iron during heating to form an Fe-Al-Si intermetallic compound layer, thus blocking oxygen. However, Al-Si coatings are expensive, significantly increasing raw material costs. Furthermore, this coating is prone to microcracks during heating, and special removal of the coating from the weld area is required during laser welding; otherwise, weld quality will be severely compromised. The second approach uses anti-oxidation coatings. Operators typically apply the coating to the steel sheet surface before heating to form a protective film at high temperatures. However, existing coatings often suffer from uneven application, limited high-temperature protection, and easy peeling of the protective film during hot stamping. Moreover, most coatings require additional cleaning after stamping, reducing production efficiency. Therefore, a comprehensive solution is urgently needed that can solve the high-temperature oxidation / decarburization problem while simultaneously providing excellent self-lubricating properties. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide an integrated hot stamping forming method and system for ultra-large automotive double door rings. The components of the precursor fluid can undergo cascade chemical reactions, transforming in situ into a uniform and dense amorphous metaphosphate-borate composite ceramic lubricating protective layer. This avoids surface decarburization and oxide scale formation, significantly reduces the friction coefficient between the sheet metal and the mold, and ensures that the double door ring parts have excellent surface hardness, bending fatigue life, and high-temperature self-lubricating properties after hot stamping.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A method for integral hot stamping forming of ultra-large automotive double door rings includes the following steps:

[0008] S0, Laser welding: Multiple bare steel plates are laser welded according to the double door ring design outline to obtain an integrated double door ring welded plate;

[0009] S1. Cleaning: Perform surface cleaning treatment on the double-door ring welded plate;

[0010] S2. Coating precursor: A layer of aqueous suspension precursor liquid is coated on the cleaned surface of the welded plate. The precursor liquid is a mixture of ammonium metaphosphate, sodium metaborate and nano silica sol.

[0011] S3. Drying: Dry the coated welded board to form a solid dry film;

[0012] S4. In-situ reaction and austenitization: The welded plate with dry film is placed in a heating furnace. During the heating process, an amorphous composite ceramic protective layer is generated in situ, and the austenite transformation is completed at the same time.

[0013] S5. Hot stamping and quenching: The heated welded plate is transferred to the hot stamping die, and hot stamping and pressure holding quenching are performed in sequence to obtain the double door ring product.

[0014] Preferably, the mass fractions of each component in the aforementioned precursor fluid are: ammonium metaphosphate 20%-50%, sodium metaborate 8%-20%, nano silica sol 3%-15%, and the remainder is deionized water.

[0015] Preferably, the method for preparing the aforementioned precursor fluid is as follows:

[0016] Ammonium metaphosphate and sodium metaborate were added to deionized water and stirred until completely dissolved. Then, nano-silica sol was added and ultrasonically dispersed. The dispersed mixture was filtered to obtain the precursor fluid.

[0017] Preferably, the dissolution temperature is 40-60℃, and the ultrasonic dispersion is performed for 5-15 minutes.

[0018] Preferably, in step S2, the thickness of the wet film is 30-50 μm, and the amount of precursor liquid used per square meter is 30-60 g; in step S3, after drying, the mass of the solid dry film formed on the surface of the double-ring welded plate is 12-25 g / m². 2 .

[0019] Preferably, in step S3, the drying temperature is 100-120℃ and the time is 1-2 minutes.

[0020] Preferably, in step S4 above, the furnace temperature is 900-930℃, and the holding time is 1.5-2 min / mm based on the plate thickness.

[0021] Preferably, in step S5, the transfer time for transferring the welded plate to the hot stamping die is less than 5 seconds; in the pressure holding and quenching step, the pressure holding pressure after mold closing is 10-20 MPa, the cooling rate is not less than 30℃ / s, and the pressure holding time is 8-12 seconds.

[0022] The integrated hot stamping forming system includes, in sequence, the following components:

[0023] Laser welding unit is used to weld multiple bare steel plates into a single double-door ring welded plate;

[0024] Surface cleaning unit for cleaning the surface of the welded plates;

[0025] A coating unit is used to coat the surface of the cleaned welded board with a precursor liquid;

[0026] An infrared drying unit is used to dry the coated welded panels to form a solid dry film.

[0027] The heating unit is used to heat the welded plate with dry film in austenitic form and generate an amorphous composite ceramic protective layer in situ.

[0028] A rapid transfer unit is used to quickly transport the heated welded plates to the hot stamping die;

[0029] The hot stamping unit is used for hot stamping and pressure holding quenching of sheet metal.

[0030] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0031] In this invention, the components of the precursor fluid can undergo cascade chemical reactions to transform in situ into a uniform and dense amorphous metaphosphate-borate composite ceramic lubricating protective layer. This protective layer has extremely low oxygen ion and carbon atom diffusion coefficients, which can prevent oxygen in the furnace gas from penetrating into the steel matrix and lock carbon atoms on the steel plate surface, avoiding surface decarburization and oxide scale formation. Furthermore, this protective layer exhibits excellent micro-viscoelasticity at 900℃, significantly reducing the friction coefficient between the sheet and the die, and ensuring that the double-door ring parts have excellent surface hardness, bending fatigue life, and high-temperature self-lubricating properties after hot stamping. Detailed Implementation

[0032] To clearly illustrate the technical features of this solution, the following detailed implementation method will be used to describe the solution.

[0033] The integrated hot stamping forming method for the ultra-large automotive double door ring of the present invention includes the following steps:

[0034] (1) Plate preparation and laser welding

[0035] Bare steel plates of different thicknesses and strengths are laser-welded according to the design contour of an ultra-large double door ring to form an integrated welded plate. The laser power is 46 kW, the welding speed is 35 m / min, the shielding gas is argon, and the flow rate is 15-20 L / min. No grinding or additional treatment is required after welding, and the original state of the bare steel surface is maintained to meet the differentiated strength requirements of different parts of the door ring.

[0036] (2) Surface cleaning

[0037] The welded plates are cleaned by online plasma cleaning or light alkaline cleaning followed by deionized water rinsing to remove surface oil and dust. The plasma cleaning power is 35 kW and the processing speed is 12 m / min. Alternatively, alkaline cleaning is performed at a temperature of 50-60℃ for 30 seconds, followed by drying with 80℃ hot air.

[0038] (3) Coating with precursor fluid

[0039] After cleaning, a layer of aqueous suspension precursor liquid is uniformly coated onto the surface of the welded plate using roller coating or aerosol spraying equipment. This precursor liquid is prepared by mixing 20%-50% ammonium metaphosphate (NH4PO3), 8%-20% sodium metaborate (NaBO2), and 3%-15% nano-silica sol (SiO2, particle size 20-50 nm, solid content 30%) with the remainder being deionized water. The viscosity is controlled at 50-150 mPa·s, the wet film thickness is 30-50 μm, and the amount of precursor liquid used per square meter is 30-60 g. During preparation, ammonium metaphosphate and sodium metaborate are first dissolved in deionized water at 40-60℃ and stirred until completely dissolved. Then, nano-silica sol is added and ultrasonically dispersed for 5-15 min. The mixture is then filtered through a 200-mesh filtration system before use.

[0040] (4) Online drying

[0041] The coated welded plates are continuously passed through an infrared drying zone at 100-120℃ for 1-2 minutes to evaporate moisture, leaving a solid dry film on the steel plate surface composed of ammonium metaphosphate, sodium metaborate, and nano-silica. After drying, the solid dry film formed on the surface of the double-door ring welded plate has a mass of 12-25 g / m³. 2 The dry film is free of cracks and has an adhesion level of ≥1.

[0042] (5) Austenitizing heating and in-situ self-assembly

[0043] The dried welded plates are fed into a roller hearth continuous heating furnace and subjected to austenitizing heating at 900-930℃ in an air atmosphere, with a holding time calculated based on a plate thickness of 1.5-2 min / mm. During the heating process, the cascade chemical reaction is as follows:

[0044] At 250-400℃, ammonium metaphosphate decomposes upon heating, releasing ammonia gas and generating highly reactive hypermetaphosphate (HPO3) in situ.

[0045] ;

[0046] At 500-600℃, hypermetaphosphoric acid undergoes dehydration and condensation to form a phosphorus pentoxide network intermediate:

[0047] ;

[0048] At 700-900℃, highly reactive P2O5 melts with sodium metaborate and nano-SiO2 particles on the surface of a steel plate and undergoes an inorganic copolymerization network reaction. Through the sharing of vertices oxygen atoms by phosphorus-oxygen tetrahedra, boron-oxygen trigonometric prisms, and silicon-oxygen tetrahedra, they are in-situ cross-linked and assembled into a three-dimensional amorphous Na-Si-BPO multi-element composite glassy network framework structure.

[0049] ;

[0050] This layer is in a molten state at high temperatures, adaptively sealing all micropores on the steel surface, while the steel plate completes the austenitic transformation.

[0051] (6) Rapid material discharge and transfer

[0052] After heating, the sheet metal is quickly conveyed to the hot stamping die by the roller conveyor of the roller hearth furnace. The transfer time is controlled within 5 seconds, and a heat preservation protective cover is set to reduce heat loss. This ensures that the surface temperature of the sheet metal is ≥800℃ and the core temperature is ≥850℃ before entering the die, thereby ensuring that the steel plate is still in the austenitic region and the surface amorphous layer remains in a low viscosity molten state during stamping.

[0053] (7) Hot stamping

[0054] After the sheet metal enters the mold with a rapid water cooling channel, it is hot stamped by a hydraulic press (clamping force ≥1500 t) at a forming speed of 50-150 mm / s.

[0055] (8) Pressure holding quenching

[0056] Immediately after mold closing, apply a holding pressure of 10-20 MPa, and simultaneously introduce cooling water into the mold cooling channel for in-mold quenching. The cooling rate is ≥30℃ / s, and the holding pressure time is 8-12 s, until the sheet temperature drops below 150℃.

[0057] (9) Mold opening and air cooling

[0058] Open the mold, use a robotic arm to remove the stamped part, and let it air cool to room temperature. At this time, the surface of the part is grayish-white or light yellow, without oxide scale and decarburized layer, and the surface quality can be directly inspected by visual inspection.

[0059] The present invention also provides an integrated hot stamping forming system, which is arranged sequentially along the production line and includes a laser welding unit, a surface cleaning unit, a coating unit, an infrared drying unit, a heating unit, a rapid transfer unit, a hot stamping unit, a cooling water circulation system, a part picking and inspection unit, and a PLC+SCADA control system for the entire production line, so as to realize the collaborative and automated production of the entire process.

[0060] Example 1

[0061] Hot stamping is performed according to the process steps of this invention, and the specific process parameters are as follows:

[0062] The precursor solution comprises the following components: 24% ammonium metaphosphate, 10% sodium metaborate, 6% nano-silica sol, and 60% water, with a viscosity of 110 mPa·s (25℃). The wet film thickness is controlled at 40 μm, and the dry film mass is approximately 45 g per square meter. Infrared drying is performed at 110℃ for 1.5 min, resulting in a dry film mass of approximately 16 g / m². 2 The austenitizing heating temperature is set at 910℃, and the holding time is calculated at 1.8 min / mm based on the plate thickness. The transfer time from the plate being pulled out of the furnace to the mold closing time is controlled at approximately 4.5 s. The pressure holding and quenching mold closing pressure is 15 MPa, the quenching cooling rate is 35℃ / s, and the pressure holding time is 10 s.

[0063] Example 2

[0064] The process steps are the same as in Example 1, the difference lies in the specific process parameters:

[0065] The precursor solution comprises the following components: 20% ammonium metaphosphate, 17.5% sodium metaborate, 12.5% ​​nano-silica sol, and 50% water, with a viscosity of 55 mPa·s (25℃). The wet film thickness is 35 μm, the dosage is 38 g per square meter, the infrared drying temperature is 100℃, and the drying time is 2 min. The dry film mass after drying is approximately 13 g / m². 2 The heating temperature is 900℃, and the holding time is 2.0 min / mm. The transfer time in hot drawing is 4.0 s, the mold closing pressure is 10 MPa, the cooling rate is 30℃ / s, and the holding time is 12 s.

[0066] Example 3

[0067] The process steps are the same as in Example 1, the difference lies in the specific process parameters:

[0068] The precursor solution comprises the following components: 48% ammonium metaphosphate, 9% sodium metaborate, 3% nano-silica sol, and 40% water, with a viscosity of 145 mPa·s (25℃). The wet film thickness is 48 μm, the dosage is 55 g / m², the infrared drying temperature is 120℃, and the time is 1 min. The dry film mass after drying is approximately 22 g / m². 2 The austenitizing temperature was set at 930℃, and the holding time was 1.5 min / mm. The transfer time was 4.8 s, the holding pressure was 20 MPa, the cooling rate was 45℃ / s, and the holding time was 8 s.

[0069] Comparative Example 1

[0070] This comparative example is basically the same as Example 1, except that steps 2-5 are omitted, that is, after laser welding and cleaning, no precursor liquid is applied, and the bare steel plate is directly sent into the heating furnace for austenitization.

[0071] Comparative Example 2

[0072] This comparative example is basically the same as Example 1, except that the bare steel plate in step 1 is replaced with a steel plate of the same base material (22MnB5) but with a 25μm thick Al-Si coating pre-plated on the surface. Before laser welding, the Al-Si coating on the edge of the weld seam is not physically or chemically removed, and the butt laser welding is performed directly. After welding, the whole is not protected by a coating and is directly sent into a roller hearth furnace for austenitizing heating and hot stamping holding quenching.

[0073] Comparative Example 3

[0074] This comparative example is basically the same as Example 1, except that the precursor fluid includes 50% ammonium metaphosphate and 50% nano silica sol, and sodium metaborate is not added.

[0075] Performance testing

[0076] (1) Surface quality and antioxidant performance test

[0077] Oxide scale grade assessment: After hot stamping, the parts are air-cooled to room temperature, and the oxide scale coverage and ease of peeling are assessed by visually comparing with the standard chart according to standard GB / T 8923.1-2011.

[0078] Oxidation weight gain test: Cut a 50mm×50mm sample from each product, weigh the mass m0 before hot stamping and the mass m1 after hot stamping (removing floating dust) using a precision balance (accuracy 0.1mg), and calculate the oxidation weight gain rate Δm=(m1-m0) / m0×100%.

[0079] Decarburization layer depth determination: According to standard GB / T224-2019, after the sample is mounted, ground and polished, it is etched with 4% nitric acid alcohol. The distance from the surface to the full martensite structure is observed under an optical microscope. The total decarburization layer depth is measured and the average value of 5 points is taken. The specific results are shown in Table 1.

[0080] Table 1. Test results of product surface quality and antioxidant properties

[0081]

[0082] As shown in Table 1, the oxidation weight gain rates of Examples 1-3 were all below 0.01%, almost zero, and there was no oxide scale on the surface. This indicates that the amorphous composite ceramic protective layer generated by the in-situ reaction of the precursor of the present invention is dense and uniform, effectively isolating oxygen in the high-temperature furnace gas and inhibiting the diffusion of carbon atoms on the surface of the steel substrate, thus achieving excellent anti-oxidation and anti-decarburization effects. The oxidation of Comparative Example 1 was extremely severe, forming a thick and difficult-to-remove oxide scale, accompanied by significant decarburization, which would seriously damage the fatigue performance and dimensional accuracy of the parts. The oxidation weight gain rate of Comparative Example 2 was even higher than that of the bare plate. This is because the Al-Si coating was not removed before laser welding, and the Al-Si coating in the weld area severely contaminated the molten pool, resulting in a large number of pores, inclusions, and cracks in the weld and heat-affected zone. The precursor in Comparative Example 3 lacked sodium metaborate and consisted only of ammonium metaphosphate and nano silica. Although it could form a partial protective layer, the P-Si-O network structure formed was incomplete and had many defects due to the lack of boron-oxygen trigonometric bodies as network modifiers and crosslinking promoters. The density was insufficient, and oxygen could still penetrate along the network defects, resulting in significant oxidative weight gain and decarburized layers.

[0083] (2) Surface hardness and tribological property testing

[0084] Surface Vickers hardness: According to standard GB / T 4340.1-2009, after hot stamping, a load of HV1, 1 kgf is applied to the surface of the part, held for 15 seconds, and the average value is taken at 10 points.

[0085] High-temperature friction coefficient test: Simulating hot stamping conditions, the plate samples of each embodiment and comparative example after hot stamping were heated to 800℃ using a high-temperature friction and wear testing machine. The grinding ball was Si3N4 (6mm in diameter), the load was 10N, the sliding speed was 50mm / s, and the stroke was 10mm. The average friction coefficient in the stable stage was recorded. The specific results are shown in Table 2.

[0086] Table 2 Vickers hardness and coefficient of friction of product surfaces

[0087]

[0088] As shown in Table 2, Examples 1-3 exhibit high surface hardness and low high-temperature friction coefficient. This is because the crystalline ceramic layer prevents surface decarburization, and the amorphous composite ceramic protective layer displays unique micro-viscoelasticity at high temperatures, forming a uniform lubricating film with low shear strength. Comparative Example 1 shows surface decarburization forming a low-hardness ferrite layer, resulting in a significant decrease in hardness. The oxide scale is rough and easily peels off, leading to high friction. In Comparative Example 2, severe oxidation and decarburization of the weld and heat-affected zone cause a sharp decrease in hardness in this area. Simultaneously, the Fe-Al-Si intermetallic compound layer formed by the Al-Si coating at high temperatures is brittle, and the addition of oxide scale results in the highest friction coefficient. Comparative Example 3 has a lower hardness than the Examples but higher than the Comparative Examples. However, due to the incomplete formation of the P-Si-O network, its lubrication performance at high temperatures is far inferior to the boron-containing three-dimensional network structure, and its friction coefficient is significantly higher than that of the Examples.

[0089] (3) Bending fatigue performance test

[0090] According to standard ISO 14125, 80mm × 15mm rectangular specimens were cut from the B-pillar region (1.8mm thick) of each embodiment and comparative product, and three-point bending fatigue tests were conducted. The span was 60mm, the stress ratio R=0.1, the frequency was 25Hz, and the maximum loading stress was 80% of the bending strength. The number of cycles (N) at which the specimen fractured was recorded. The median value of 5 specimens in each group was taken. The specific results are shown in Table 3.

[0091] Table 3 Bending fatigue properties of the products

[0092]

[0093] As shown in Table 3, Example 1 exhibits the highest fatigue life with no surface defects. In Comparative Example 1, surface oxide peeling pits become the preferred sites for fatigue crack initiation, leading to a significant decrease in fatigue life. Comparative Example 2 shows the lowest fatigue life; the welding defect area caused by the untreated Al-Si coating becomes the weakest link, rapidly initiating and propagating cracks under cyclic loading, resulting in early fracture. Comparative Example 3 demonstrates a better fatigue life than the Comparative Example, but significantly lower than Example 1. This is because the boron deficiency leads to an incomplete protective layer, causing localized oxidation / decarburization and limiting further improvement in fatigue performance.

[0094] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any way, and all technical solutions obtained by equivalent substitution or equivalent transformation fall within the protection scope of the present invention.

Claims

1. A method for integral hot stamping forming of an ultra-large automotive double door ring, characterized in that, Includes the following steps: S1. Cleaning: Perform surface cleaning treatment on the double-door ring welded plate; S2. Coating precursor: A layer of aqueous suspension precursor liquid is coated on the cleaned surface of the welded plate. The precursor liquid is a mixture of ammonium metaphosphate, sodium metaborate and nano silica sol. S3. Drying: Dry the coated welded board to form a solid dry film; S4. In-situ reaction and austenitization: The welded plate with dry film is placed in a heating furnace. During the heating process, an amorphous composite ceramic protective layer is generated in situ, and the austenite transformation is completed at the same time. S5. Hot stamping and quenching: The heated welded plate is transferred to the hot stamping die, and hot stamping and pressure holding quenching are performed in sequence to obtain the double door ring product.

2. The integrated hot stamping forming method according to claim 1, characterized in that, The mass fractions of each component in the precursor fluid are as follows: ammonium metaphosphate 20%-50%, sodium metaborate 8%-20%, nano silica sol 3%-15%, and the remainder is deionized water.

3. The integrated hot stamping forming method according to claim 2, characterized in that, The method for preparing the precursor fluid is as follows: Ammonium metaphosphate and sodium metaborate were added to deionized water and stirred until completely dissolved. Then, nano-silica sol was added and ultrasonically dispersed. The dispersed mixture was filtered to obtain the precursor fluid.

4. The integrated hot stamping forming method according to claim 3, characterized in that, The dissolution temperature is 40-60°C, and the ultrasonic dispersion is performed for 5-15 minutes.

5. The integrated hot stamping forming method according to claim 1, characterized in that, In step S2, the thickness of the coated wet film is 30-50 μm, and the amount of precursor liquid used per square meter is 30-60 g; in step S3, after drying, the mass of the solid dry film formed on the surface of the double-ring welded plate is 12-25 g / m². 2 .

6. The integrated hot stamping forming method according to claim 1, characterized in that, In step S3, the drying temperature is 100-120°C and the time is 1-2 minutes.

7. The integrated hot stamping forming method according to claim 1, characterized in that, In step S4, the furnace temperature is 900-930°C, and the holding time is 1.5-2 min / mm based on the plate thickness.

8. The integrated hot stamping forming method according to claim 1, characterized in that, In step S5, the transfer time for transferring the welded plate to the hot stamping die is less than 5 seconds; in the pressure holding and quenching step, the pressure holding pressure after mold closing is 10-20 MPa, the cooling rate is not less than 30°C / s, and the pressure holding time is 8-12 seconds.

9. The system for the integrated hot stamping forming method according to any one of claims 1-8, characterized in that, The processing sequence includes, in order: Surface cleaning unit for cleaning the surface of the welded plates; A coating unit is used to coat the surface of the cleaned welded board with a precursor liquid; An infrared drying unit is used to dry the coated welded panels to form a solid dry film. The heating unit is used to heat the welded plate with dry film in austenitic form and generate an amorphous composite ceramic protective layer in situ. A rapid transfer unit is used to quickly transport the heated welded plates to the hot stamping die; The hot stamping unit is used for hot stamping and pressure holding quenching of sheet metal.